Effect of ischemic injury characteristics on left ventricular systolic function in patients with acute myocardial infarction - V. E. Oleinikov; L. I. Salyamova; N. A. Donetskskaya; A. V. Vdovkin (Российский кардиологический журнал)
Aim. To study laboratory and magnetic resonance imaging (MRI) characteristics of infarction area depending on left ventricular (LV) global systolic function in patients with acute myocardial infarction (AMI) after revascularization.Material and methods. A total of 78 patients with primary AMI were included. On days 7-10, contrast-enhanced cardiac MRI was performed. Blood brain natriuretic peptide (BNP) was analyzed. Cardiac MRI was used to determine the characteristics of scar tissue, peri-infarct zone (PIZ), microvascular obstruction (MVO), intramyocardial hemorrhage (IMH) and the global contrast index.Results. According to the MRI, patients were divided into following groups: group 1 — LV ejection fraction (LVEF) ≥50% (n=50), group 2 — LVEF 40-49% (n=21), group 3 — LVEF <40% (n=7).The BNP in groups 1, 2, 3 was 106,8 (37,5; 248), 232,6 (170,1; 337,7) and 548,5±236,4 ng/ml, respectively (p1-3<0,05). The scar tissue mass in groups 1, 2, 3 was 10,3 (2,4; 20,0), 34,7±21,3, 59,4±37,6 g, respectively (p1-2, 3<0,01). PIZ differences were found only between patients with preserved and mildly reduced EF. MVO was diagnosed in 26% of patients with LVEF ≥50%, in 47,6% of patients with LVEF of 40-49% and 85,7% with LVEF <40% (p1-3<0,01). The detection rate of IMH prevailed in the 2nd group (33,3%) compared with the 1st group (12%) (p1-2<0,05). The global contrast index was the lowest in the 1st group (14,7 (8,8; 27,9)%), intermediate in the 2nd group (33,3±12,6%), the highest in the 3th group (54,2±19,5%) (р1-2, 3; 2-3<0,05).Conclusion. The following risk factors for a decrease in LV systolic function in patients with AMI after revascularization were identified: the size of scar tissue, PIZ, MVO and IMH characteristics, global contrast index, BNP level.